Financial appraisal of broilers farm in Johor Malaysia - Bakar, Sofiah (2018)
This study is related to the financial evaluation of broiler farming farms in the State of Johor. This study examines the financial position of broiler farming farms located in several districts in Johor such as Muar, Kluang and Pontian by using capital budgeting techniques and production cost analysis. The capital budgeting method includes the calculation of net present value (NPV), internal rate of return (IRR), profitability index and payback period while cost analysis is used to identify fixed costs, variable costs, net returns and input and output ratio. The production and expenditure information for broiler farms in Johor were collected from 94 farms in several districts by using simple random sampling. The data used for this research were obtained from the Institute of Policy Studies on Agriculture and Food, UPM. Data include basic farmers information, initial business capital, the number of day old chicken (DOC) per round, broiler feed information and some others. These data are analysed to identify the financial performance of the broiler industry in Johor. Sensitivity analysis is used to evaluate the effect of increasing cost of broilers feed, the increase in the cost of building the coop system and a reduction of selling price at farm level. The findings show that feed cost is the highest cost for broiler production. Another things such as increasing cost to build the coop and decreasing of selling price also analysed using sensitivity analysis to identify the impact of changes on the broilers farm financial system.